(untitled) (KULT_online, 2024)
Configurations of Migration, edited by Jennifer Leetsch, Frederike Middelhoff, and Miriam Wallraven, links media representations of migration with knowledge about migration. In the form of a selection of articles, interviews, short stories, and personal essays collected from an online conference in 2021, the book presents a wide range of perspectives on migration. It enriches the field of migration studies by giving voice to a diverse range of writers, scholars, and artists from around the world.